Modeling bacterial interactions uncovers the importance of outliers in the coastal lignin-degrading consortium - Qiannan Peng; Cheng Zhao; Xiaopeng Wang; Kelin Cheng; Congcong Wang; Xihui Xu; Lu Lin (Nature Communications)
Abstract Lignin, as the abundant carbon polymer, is essential for carbon cycle and biorefinery. Microorganisms interact to form communities for lignin biodegradation, yet it is a challenge to understand such complex interactions. Here, we develop a coastal lignin-degrading bacterial consortium (LD), through “top-down” enrichment. Sequencing and physiological analyses reveal that LD is dominated by the lignin degrader Pluralibacter gergoviae (>98%), with additional rare non-degraders. Interestingly, LD, cultured in lignin-MB medium, significantly enhances cell growth and lignin degradation as compared to P. gergoviae alone, implying a role of additional outliers. Using genome-scale metabolic models, metabolic profiling and culture experiments, modeling of inter-species interactions between P. gergoviae, Vibrio alginolyticus, Aeromonas hydrophila and Shewanella putrefaciens, unravels cross-feeding of amino acids, organic acids and alcohols between the degrader and non-degraders. Furthermore, the sub-population ratio is essential to enforce the synergy. Our study highlights the unrecognized role of outliers in lignin degradation.